Efektivitas Ekstrak Strobilanthes crispus terhadap Kadar Glukosa Darah Puasa dan Pasca Tes Toleransi Glukosa Oral pada Rattus norvegicus Diabetes Melitus - Gunawan, Alvin; Wihanto, Laura; Muliono, Ari Christy (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. The 2018 Riskesdas data shows that the prevalence of diabetes mellitus is increasing each year. Strobilanthes crispus leaves are known for lowering blood glucose levels. This study aimed to determine the difference in the effectiveness of S. crispus leaves ethanolic extract on fasting blood glucose (FBG) and post-oral glucose tolerance test (OGTT). Methods. True experimental study using post-test only control group design and Rattus norvegicus as experimental animals. Rattus norvegicus were selected by random sampling which were then divided into 4 groups (K, P1, P2, P3), each group consisted of 5 animals. The animals were subsequently induced with diabetes mellitus via a single injection of 160 mg/kgBW/IP alloxan. Group K was given 0.5% NaCMC solution at a dose of 1 ml/200 g BW/day/oral/day. Group P1, P2, and P3 received extract at a dose of 100, 400, 600 mg/kg BW/oral/day for 21 days using oral gavage. Statistical analysis was performed using ANOVA, Tukey, Brown-Forsythe, and Kruskal-Wallis tests. Results. Mean FBG level in group K, P1, P2, P3 were 338.40 mg/dL, 270.80 mg/dL, 200.00 mg/dL, and 138.60 mg/dL, respectively. Mean value of 60 minutes OGTT blood glucose level in group K, P1, P2, P3 were 355.60 mg/dL, 289.00 mg/dL, 188.00 mg/dL, and 164.40 mg/dL, respectively. Meanwhile, mean value of 120 minutes OGTT blood glucose level in group K, P1, P2, P3 were 346.60 mg/dL, 236.20 mg/dL, 175.40 mg/dL, and 117.20 mg/dL, respectively. The hypothesis test results showed a significant difference in 120 minutes OGTT blood glucose level (p= 0.031). Conclusion. The use of ethanol extract from S. crispus leaves is more beneficial in reducing blood glucose levels in 120 minutes OGTT compared to FBG level and 60 minutes OGTT level, with the highest reduction observed in the group given a dose of 600 mg/kgBW/oral/day compared to control. Keywords: DM, fasting blood glucose, OGTT, Rattus norvegicus, Strobilanthes crispus